FOREIGN CURRENCY RISK HEDGING - Mihaela SUDACEVSCHI (Challenges of the Knowledge Society)
This paper presents the traditional types of exchange rate risk faced by firms and some of principal methods of exchange risk management that a company which make foreign currency operations can use. Foreign currency risk management involves both assessing the risk faced by the companies and adopting measures for the risk hedging or reduce the damage it may cause. The damages result from the company’s unfavorable difference between the exchange rates of the currencies in which the transactions are made.